Circulatory reflexes in myocardial infarction. Issue 2 (February 1977) - Kirby, B J
Abstract : The Valsalva manoeuvre was used to examine circulatory reflexes in 22 patients with acute myocardial infarction. Four patients had the 'square wave' response of cardiac failure and two responded normally to the manoeuvre. In the remaining 18 patients there was a 20 per cent or more fall in pulse pressure during the manoeuvre, but no ensuing rise in diastolic pressure, implying impairment of vasoconstriction. This impairment cannot be explained by acidosis, hypocapnia, or arterial hypoxaemia but may be explained by reflex inhibition of vasoconstriction. This abnormal response has important implications when transporting patients; furthermore, it could explain the rapid deterioration sometimes seen in patients with arrhythmias.